Is There a Taxane-Free Interval That Predicts Response to Taxanes as a Later-Line Treatment of Recurrent Ovarian or Primary Peritoneal Cancer?. Issue 3 (1st March 2009) - McCourt, Carolyn; Dessie, Sybil; Bradley, Ann Marie; Schwartz, Joanna; Brard, Laurent; Dizon, Don S.
Abstract : Objectives: Taxanes have reported response rates of 20% to 40% in recurrent ovarian cancer (ROC) but are less well studied as a later-line treatment. We reviewed our experience with taxanes in ROC to determine (1) if a taxane-free interval is associated with response rates in women with ROC and (2) if the use of intervening therapy (IT) affects subsequent response rates to taxanes. Methods: We retrospectively identified women who received first- or second-line platinum-taxane therapy and later received a single-agent taxane. Demographics, intervening regimens, and follow-up and survival data were collected. Responses were characterized by cancer antigen 125 levels based on the Gynecologic Cancer InterGroup serologic response definitions. Results: We identified 46 women who met the eligibility criteria. The median age was 57 years (range, 39-78 years). The median interval between taxanes was 25.8 months (range, 2.9-85.5 months), with 10 (21%) of the women were treated 12 months or less from their last taxane and 37 (79%) treated more than 12 months. The median number of IT was 2 (range, 0-5). Forty patients (87%) received paclitaxel; 6 (13%) received docetaxel. All patients treated 12 months or less from their last taxane responded ( P = 0.02). The number of IT was associated with a better response; all women (100%) treated who had no IT, 7 (54%) of 13 women with 1 to 2 ITs, and 7 (39%) of 18 women with 3 ITs or more responded. The overall survival was 13.4 months in responders versus 10.6 months in nonresponders ( P = 0.27). Conclusions: Taxanes maintain an activity as a later-line agent, even with 3 or more intervening therapies. However, the highest responses were seen if taxanes were used within 12 months of the last platinum-based combination. The lack of an increased response with aprolonged taxane-free interval is likely related to the number of IT, consistent with the emergence of multidrug resistance.